Relationship between Anxiety Level and Blood Pressure Level Pre Cataract Surgery One Day Care - Larasati, Fitri; Wardani, Yulia; Kurniasari, Cecilia Indri (Lentera Perawat, 2025)
Aging in the elderly is often accompanied by various health problems, one of which is cataracts. Cataract surgery is an effective solution but often causes anxiety in patients, which can affect their blood pressure before surgery. This study aims to determine the relationship between the anxiety level of the elderly and pre-operative blood pressure in cataract one day care. This research uses a quantitative method with a descriptive correlational design and a cross-sectional approach. The research sample consisted of 40 respondents selected using consecutive sampling techniques. Data were collected using the Amsterdam Preoperative Anxiety and Information Scale (APAIS) questionnaire and blood pressure measurements with a sphygmomanometer. The analysis results showed a significant and positive relationship between anxiety levels and pre-operative blood pressure in cataract one day care with a p-value of 0.000 and a correlation strength (r) of 0.955. High anxiety levels in elderly patients undergoing cataract surgery are associated with increased pre-operative blood pressure. It is crucial for the health professionals to manage patients' anxiety through psychological interventions and education before surgery to reduce the risk of elevated blood pressure that can affect surgical safety.